Exploring “Kaulinan Barudak” to Develop Children’s Character Values in Islamic Early Childhood Education - Mubiar Mubiar; Nordin Bin Mamat; Ernawulan Syaodih (Jurnal Pendidikan Islam, 2020)
In RA (Raudhatul Athfal/Islamic Early Childhood Education) context, since many teachers relied heavily on standard learning guidelines, most of them didn’t have the power of creativity to make learning for children fun.  As a result, children were likely to experience burn out and this calls for a solution to apply like kaulinan barudak to develop children’s character values. This study was aimed at determining the effectiveness of the implementation of kaulinan barudak, Sundanese traditional games in developing character values for children in RA (Raudhatul Athfal/Islamic Early Childhood Education). This research applied a quasi-experimental method with Nonequivalent Pretest-Posttest design. This research was conducted in two RA schools namely RA Al Muqadasah 1 and RA Al-Muqadasah 2 with 36 children involved. The test result for average difference on the post-test showed that children’s character values of the experimental class and the control class at the 0.05 significance level was obtained p (sig. (2-tailed) = 0,000. This indicated that there was a significant difference between the average score of the experimental class and control class in their post-test in terms of their character values scores at a level of confidence of 95%. Applying kaulinan barudak provided the experimental class a fun learning experience, potential growth, fun game, peer interaction, and a pleasant atmosphere. The process allowed character values to occur and children learned those values and realized them in kaulinan barudak.